38.5k views
0 votes
Which of the following statements is true about the following equation?

-18 - 3x = 12

-3x = 6

x =-2



(A) It is correct.

(B) The 6 should be 30 in step two.

(C) The 6 should be -6 in step two.

(D) The 6 should be -4 in step two.

2 Answers

2 votes

Answer:

B. The 6 should be 30 in step two.

Explanation:

User Sajjad Ali Khan
by
5.5k points
4 votes

Answer:

B: The 6 should be 30 in step 2 of the problem

Explanation:

Step 1:

- 18 - 3x = 12 Equation

Step 2:

- 3x = 30 Add 18 on both sides

Step 3:

0 = 30 + 3x Add 3x to both sides

Step 4:

- 30 = 3x Subtract 30 on both sides

Step 5:

- 30 ÷ 3 Divide

Step 6:

x = - 10

Answer:

B: The 6 should be 30 in step 2 of the problem

Hope This Helps :)

User Hiddenbit
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.